Interfaced Ag/Cu nanostructures derived from metal thiolate nanoplates: A highly selective catalyst for electrochemical reduction of CO2 to ethanol. Issue 1 (7th March 2022) - Abeyweera, Sasitha C.; Simukaitis, Matas; Wei, Qilin; Sun, Yugang
Abstract: Selective reduction of CO2 into liquid products such as ethanol through electrochemical catalysis is promising in storing renewable energy in more deliverable chemicals and balancing the carbon footprint in the environment. However, the lack of efficient catalysts for electrochemical CO2 reduction reaction (eCO2 RR) makes the promise challenging because the formation of C2+ alcohols requires coupling reactions between the shallow reduction intermediates and deep reduction intermediates that are usually difficult to form on uniform catalyst surfaces simultaneously with appropriate transient kinetics. Herein, we report a new strategy for synthesizing bimetallic nanostructures with high densities of interfaced Ag/Cu boundaries, which facilitate the coupling reaction of the high‐oxidation‐number intermediates (CO) formed on the Ag surface and the low‐oxidation‐number intermediates (CH x ) formed on the Cu surface. The synthesis relies on the electrochemical reduction of bilayered nanoplates made of silver thiolate and copper thiolate, resulting in Ag/Cu nanostructures exposing Ag surface, Cu surface, and the Ag/Cu interfaced boundaries. Balancing the accessible surface areas of the Ag surface, Cu surface, and Ag/Cu boundaries is beneficial for maximizing the activity and selectivity of eCO2 RR towards ethanol production. Faradaic efficiency of forming ethanol has been observed as high as about 50% using the Ag/Cu nanostructure catalyst with molar ratio n Ag : n Cu of 1:1. Moreover, the promoted coupling reaction at the Ag/Cu boundaries and surface modification with thiolate anions significantly suppress the undesirable hydrogen evolution reaction, particularly at high cathodic potentials, maintaining high energy efficiency for eCO2 RR. Abstract : Selective production of ethanol from electrochemical reduction of carbon dioxide (CO2 ) requires the simultaneous shallow reduction and deep reduction of CO2, forming intermediates that can couple into ethanol. Integrating silver (Ag) that favors the shallow reduction and copper (Cu) that promotes the deep reduction creates Ag/Cu interfaced boundaries, which catalyze the couple reaction of the shallow reduction intermediates and the deep reduction intermediates to form ethanol. The results shed light on the promise of heterogeneous boundaries in selective catalysis.